Terra/MODISを用いた北海道道東地方における落葉期のカラマツ人工林と落葉広葉樹林の植生フェノロジーの差異の検出 - 富田, 瑞樹; 浅沼, 市男; 原, 慶太郎; 長谷川, 大輔; 朴, 鍾杰 (Shashin sokuryō to rimōto senshingu, 2017)
Normalized Difference Water Index (NDWI), Green-Red Vegetation Index (GRVI), and other indices of remotely detected spectrum combinations have been proposed in order to evaluate the vegetation changes and distributions. The training area of artificial Japanese larch forest and deciduous broad leaved forest (Japanese white birch and Japanese oak) in Hokkaido were extracted from MODIS data based on RapidEye data and GIS data of Vegetation Survey on 6/7th National Basic Survey on Natural Environment (Biodiversity Center of Japan, Ministry of the Environment (http://www.biodic.go.jp/index_e.html)), the mean elevation, and the monthly mean temperature. The NDWI and GRVI were obtained for each training area from MODIS data. As a result, i) the MODIS GRVI of artificial Japanese larch forest were around -0.1, while the MODIS NDWI were greater than 0.5, ii) the MODIS GRVI of deciduous broad leaved forest were around 0.0, while the MODIS NDWI were less than 0.5, iii) these MODIS GRVI of Japanese larch and deciduous broad leaved forest were similar to GRVI of yellow and red leaves of larch and leafless birch calculated from the camera image of the canopy.